An unusual case of asymptomatic non-urothelial bladder tumour. (2016) - Ching, Daniel; Anastasiadis, Eleni; Sandhu, Sarb
Highlights: Bladder paragangliomas are rare and account for less than 0.05% of all bladder tumours. They can present as incidental findings without any clinical symptoms. Due to the non-specific nature, they are often not part of the urologists differential diagnoses. Pre-operative suspicion and management are essential to reduce anaesthetic risk. Abstract: Introduction: Non-urothelial tumours are rare and account for less than 5% of all bladder tumours. Bladder paragangliomas also known as extra-adrenal pheochromocytomas are of the non-urothelial subgroup. We present an unusual case of asymptomatic bladder paraganglioma. Case report: A 77 year old lady presented with acute abdominal pain was found to have an incidental enhancing nodule in the bladder. During cystoscopy and transurethral resection the patient experienced significant fluctuations in blood pressure that required anaesthetic adjustments. Review of histology confirmed a diagnosis of bladder paraganglioma. Discussion: Most bladder paraganglioma cases present with sympathomimetic related symptoms and microscopic haematuria but our patient was asymptomatic which resulted in inadequate pre-operative optimisation and high anaesthetic risk. Majority of paragangliomas are benign but there is a 20-40% chance of malignancy. The management options will predominantly depend on whether disease is localised, regional, metastatic or recurrent in nature. Conclusion: Due to the non-specific nature of disease, variability of presentations and rare incidence, bladder paragangliomas are often not part of the urologists' differential diagnoses. In our opinion, establishing guidelines should assist to achieve a balance between anaesthetic risks, cystoscopy and follow up.